A Hybrid FEM/DEM Approach to Estimating Rock Block Breakage due to Gravity Free-Fall. Issue 1 (August 2021) - Veltin, K; Elmo, D; Rogers, S
Abstract: An understanding of the fragmentation of rock blocks from gravity free-fall has applications to rock fall analysis as well as block cave mining. In the case of a rock fall, blocks splitting mechanics can reduce the overall block energy and therefore reduce the travel distance of the blocks. Conversely, splitting may result in a larger number of smaller fragments that may still pose a risk despite their reduced dimensions. In the case of block caving, splitting of blocks it is believed to aid the flow of the ore column, to reduce the potential of hang-ups, and to allow for easier extraction and processing of the ore. Traditional methods for block fragmentation analysis use empirical relationships and rule-based approaches that heavily rely on the block geometry, rather than block-to-block interactions. In this paper we present a study of fragmentation processes using a hybrid finite-element/discrete-element method (FEM/DEM). The approach is capable to account for the numerical instability generally associated with the simulation of high velocity surface interactions and subsequent fracturing. To date the analysis has focused on the simulation of free-falling blocks onto a fixed surface. The initial and final block breakage has been compared against parameters including the roughness and curvature of the impacted surface, and the rock block orientation in space during free fall. We believe the results could provide useful insight into designing catchments for rock fall, as well as an increased understanding of the complexities of secondary fragmentation estimates and the range of fragmentation that could be expected in block caving.